2019
DOI: 10.1186/s40425-019-0679-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, pharmacokinetics, and pharmacodynamics of the afucosylated, humanized anti-EPHA2 antibody DS-8895a: a first-in-human phase I dose escalation and dose expansion study in patients with advanced solid tumors

Abstract: Background Erythropoietin-producing hepatocellular receptor A2 (EPHA2) is overexpressed on the cell surface in many cancers and predicts poor prognosis. DS-8895a is a humanized anti-EPHA2 IgG1 monoclonal antibody afucosylated to enhance antibody-dependent cellular cytotoxicity activity. We conducted a two-step, phase I, multicenter, open-label study to determine the safety, tolerability, and pharmacokinetics of DS-8895a in patients with advanced solid tumors. Methods St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The maximum tolerated dose was not reached in step 1 and the planned highest dose (20 mg/kg) was used in step 2. A total of 37 cases (22 and 15 in steps 1 and 2, respectively) were included, but all discontinued the study for overt disease progression (20 and 13 in steps 1 and 2, respectively) or adverse events (AEs, the remaining cases) [120]. Similarly, the NCT02004717 trial enrolled 9 patients, who did not complete the study.…”
Section: Epha2-based Clinical Developmentmentioning
confidence: 99%
“…The maximum tolerated dose was not reached in step 1 and the planned highest dose (20 mg/kg) was used in step 2. A total of 37 cases (22 and 15 in steps 1 and 2, respectively) were included, but all discontinued the study for overt disease progression (20 and 13 in steps 1 and 2, respectively) or adverse events (AEs, the remaining cases) [120]. Similarly, the NCT02004717 trial enrolled 9 patients, who did not complete the study.…”
Section: Epha2-based Clinical Developmentmentioning
confidence: 99%
“…One gastric cancer patient showed a partial response and 13 patients achieved stable disease, although the latter did not correlate with EphA2 expression in tumor biopsies, suggesting this may not be treatment-related. Consistent with DS-8895a-induced ADCC activity, a decrease in CD16-positive NK cells and a transient increase in serum inflammatory cytokines were observed after treatment [31]. A second trial to investigate imaging and safety of DS-8895a in non-Japanese patients with advanced EphA2+ tumors (NCT02252211) used more limited treatment doses and incorporated PET imaging of 89 Zr trace-labeled antibody at day 1 and 36.…”
Section: Clinical Trialsmentioning
confidence: 72%
“…To date, three anti-Eph antibodies have been tested in clinical trials. The unconjugated anti-EphA2 mAb DS-8895a has been evaluated in a Phase I trial (ClinicalTrials.gov identifier NCT02004717) in Japanese patients with advanced solid tumors [31]. The humanized mAb was afucosylated to enhance ADCC activity, improving antibody binding of the FcγRIIIa receptor (CD16), highly expressed on natural killer (NK) cells.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…In subsequent clinical trials, tumor uptake of the compound was confirmed in 100% of imaged patients [ 91 ]. Fourteen of thirty-seven patients treated with DS8895a in a phase 1 trial achieved stable disease or partial response with five reports of grade ≥ 3 cytopenia but no thrombotic or hemorrhagic events described, an improvement compared to results with MEDI-547 [ 92 ]. Bicycle Therapeutics has recently described a high-affinity EphA2 targeting peptide-cytotoxin conjugate with low affinity for other Eph proteins which dramatically reduces in vivo tumor volume in an EphA2 expression-dependent manner without hematologic adverse effects [ 93 ].…”
Section: Epha2 Therapeutics In Clinical Trials: Outcomesmentioning
confidence: 99%